Socialization of Natural Medicines and New Perspectives on Traditional Indonesian Medicine for Pharmaceutical Workers - Wibowo, Teguh Setiawan; Khotimah, Khusnul; Af’idah, Bannan Muthi’atul (Eastasouth Institute, 2024)
Treatment traditional Indonesian herbs, which have been There is during centuries, now get increasing attention big in the middle change paradigm global health towards a more approach holistic and natural. Socialization about treatment traditional This important done for give perspective new that puts forward value and potential drug made from nature. Through activity socialization, society invited for understand more in about various available herbal concoctions, how to its use, as well as benefit for health. Knowledge This No only support sustainability practice treatment traditional, but also integrate it with modern medicine. In the context of modern health, proper understanding about treatment potion traditional can answer challenge in field health, such as increasing request to treatment natural and issues resistance medicine. Through socialization of a nature educational, community can empowered in choose alternative more treatment safe and effective, and contribute to preservation culture local. In addition, socialization this also becomes bridge connecting knowledge traditional and research scientific, encouraging research more carry on about efficacy herbs drug material nature. With Thus, socialization This expected can strengthen position treatment traditional Indonesian herbs as one of the pillars in system better health inclusive and sustainable.